Inhibitory Efficacy of Arthrospira platensis Extracts on Skin Pathogenic Bacteria and Skin Cancer Cells - Ranchana Rungjiraphirat; Nitsanat Cheepchirasuk; Sureeporn Suriyaprom; Yingmanee Tragoolpua (Biology)
Arthrospira platensis (spirulina) is a cyanobacterium containing various phytochemical compounds associated with various antioxidant, antimicrobial, antiviral, anticancer, anti-inflammatory, and immune-promoting properties. The efficacy of ethanolic and methanolic crude extracts of A. platensis regarding antibacterial, antioxidant, and anticancer effects was determined in this study. The ethanolic extract showed the highest antioxidant activity by 8.96 ± 0.84 mg gallic acid equivalent per gram of extract (mg GAE/g extract), 53.03 ± 4.21 mg trolox equivalent antioxidant capacity per gram of extract (mg TEAC/g extract), and 48.06 ± 0.78 mg TEAC/g extract as determined by DPPH, ABTS, FRAP assays, respectively. Moreover, the ethanolic extract showed the highest total phenolic and flavonoid compound contents by 38.79 ± 1.61 mg GAE/g extract and 27.50 ± 0.53 mg of quercetin equivalent per gram of extract (mg QE/g extract). Gallic acid and quercetin in the extracts were also determined by HPLC. The antibacterial activity was evaluated by agar well diffusion and broth dilution methods on skin pathogenic bacteria, including Staphylococcus aureus, Staphylococcus epidermidis, methicillin-resistant S. aureus (MRSA), Micrococcus luteus, Pseudomonas aeruginosa, and Cutibacterium acnes. The inhibition zone of A. platensis extracts ranges from 9.67 ± 0.58 to 12.50 ± 0.50 mm. In addition, MIC and MBC values ranged from 31.25 to 125 mg/mL. The inhibition of biofilm formation and biofilm eradication by A. platensis ethanolic extract was 87.18% and 99.77%, as determined by the crystal violet staining assay. Furthermore, the anticancer activity of A. platensis on A375 human melanoma cells was examined. The ethanolic and methanolic extracts induced DNA apoptosis through both intrinsic and extrinsic pathways by upregulating the expression of caspase-3, caspase-8, and caspase-9. These findings suggested that A. platensis demonstrated promising antioxidant, antibacterial, and anticancer activities, emphasizing its potential as a natural therapeutic agent for the management of pathological conditions.